Study of structural, optical and electrical properties of thin Ag2Cu2O4 films prepared by pulsed laser deposition - Naji, Iqbal S. (Iraqi Journal of Physics, 2019)
The influence of sintering and annealing temperatures on the structural, surface morphology, and optical properties of Ag2Cu2O4 thin films which deposited on glass substrates by pulsed laser deposition method have been studied. Ag2Cu2O4 powders have polycrystalline structure, and the Ag2Cu2O4 phase was appear as low intensity peak at 35.57o which correspond the reflection from (110) plane. Scan electron microscopy images of Ag2Cu2O4 powder has been showed agglomerate of oxide particles with platelets shape. The structure of thin films has been improved with annealing temperature. Atomic Force micrographs of Ag2Cu2O4 films showed uniform, homogenous films and the shape of grains was almost spherical and larger grain size of 97.85 nm has obtained for film sintered at 600 °C. The optical band gap was increase from 1.6 eV to 1.65 eV when sintering temperature increased to 300 °C and decrease to 1.45 eV at 600 °C for the films deposited at room temperature. Heat treatment of films has been increased the energy band with increasing sintering temperature. Hall coefficient of Ag2Cu2O4 films have a positive sign which means the charge carrier is a p-type. The electrical conductivity decreases with increasing of the sintering temperature for as deposited and annealed films.